Analisis Usaha Peternakan Ayam Broiler Dengan Sistem Kemitraan PT Ciomas Adisatwa di Kecamatan Kepanjen (Jurnal Agribisnis Indonesia, 2025)
The study aimed to analyze the business, measure the production risks, costs, and profits of the broiler farming sector in Kepanjen Subdistrict with the partnership system of PT Ciomas Adisatwa and determine the steps taken to reduce these risks. The study used quantitative and qualitative descriptive methods. Sampling using the census method was 3 farmers who partnered with PT Ciomas Adisatwa. Primary and secondary data were used in this study. R/C, Break Even Point (BEP), Return on Investment (ROI), and Payback Period (PP) ratios are used in business analysis approaches. The formula of the Coefficient of Variation (CV) and lower limit (L) is used to analyze the magnitude of production, price, and profit risks. The findings of the business analysis show the feasibility of operation and growth of the livestock industry in Kepanjen District because the average results of the feasibility indicator R/C Ratio 1.08, BEP price, and BEP production are lower than the number of products and selling prices of broiler chickens obtained, ROI 8.01%, and PP less than a year. In collaboration with PT Ciomas Adisatwa, broiler farming companies have a production risk of 0.49. This broiler chicken farming company in collaboration with PT Ciomas Adisatwa has a price risk of 0.04. With a lower limit of IDR 229.10, this broiler farming business in partnership with PT Ciomas Adisatwa has a profit risk of 0.58. Farmer risk management is adequate and follows the guidance of PT Ciomas Adisatwa field instructor.